What makes opportunistic GP interventions effective? An analysis of behaviour change techniques used in 237 GP-delivered brief interventions for weight loss. - Bourhill, J; Lee, JJ; Frie, K; Aveyard, P; Albury, C (Oxford University Press, 2020)
Background Evidence shows that clinician-delivered brief opportunistic interventions are effective in obesity, and guidelines promote their use. However, there is no evidence on how clinicians should do this, and guidelines are not based on clinical evidence.